2013
DOI: 10.5020/18061230.2013.p539
|View full text |Cite
|
Sign up to set email alerts
|

Os efeitos do crescimento urbano sobre a dengue

Abstract: The effects of urban growth on dengueLos efectos del crecimiento urbano sobre la dengue RESUMO Objetivo: Analisar a dinâmica espacial e temporal da dengue em Coronel Fabriciano, Minas Gerais, Brasil, e associar os casos ao crescimento das áreas urbanas e à perda de áreas naturais nos últimos anos. Métodos: Trata-se de um estudo descritivo, exploratório, de abordagem quantitativa. Os casos de dengue relativos a 2009 foram obtidos na Secretaria Municipal, incluindo-se os suspeitos e os confirmados. Obtiveram-se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…In the northern region of Minas Gerais, seasonally dry, deciduous forests are considered as part of the Atlantic Forest biome by the Decree 6660/2008 but suffer high rates of deforestation even with this protection [57,58]. Several studies have already demonstrated the relationship between the incidence of arthropod-borne diseases and deforestation [6,17,25,59,60], including dengue in other regions of Brazil [4,24,27,61,62]. MacDonald and Mardoqueu [63] used the regionalization of areas in the Amazon to more effectively identify the relationship between malaria cases and deforestation, making clear the importance that native areas have for local public health.…”
Section: Discussionmentioning
confidence: 99%
“…In the northern region of Minas Gerais, seasonally dry, deciduous forests are considered as part of the Atlantic Forest biome by the Decree 6660/2008 but suffer high rates of deforestation even with this protection [57,58]. Several studies have already demonstrated the relationship between the incidence of arthropod-borne diseases and deforestation [6,17,25,59,60], including dengue in other regions of Brazil [4,24,27,61,62]. MacDonald and Mardoqueu [63] used the regionalization of areas in the Amazon to more effectively identify the relationship between malaria cases and deforestation, making clear the importance that native areas have for local public health.…”
Section: Discussionmentioning
confidence: 99%
“…In the northern region of Minas Gerais, seasonally dry, deciduous forests are considered as part of the Atlantic Forest biome by the Decree 6660/2008, but suffer high rates of deforestation even with this protection (DUPIN et al 2018;ESPÍRITO-SANTO et al 2020). Several studies have already demonstrated the relationship between the incidence of arthropod-borne diseases and deforestation (BAUHOFF & BUSCH, 2020;BURKETT-CADENA & VITTOR, 2018;CASTRO et al, 2019;ELLWANGER et al, 2020;YASOUKA & LEVINS, 2007), including dengue in other regions of Brazil (AMARAL, 2015;HORTA et al 2013;MICELI & FONSECA, 2017;OLIVEIRA, 1998;VIERO et al, 2013). MacDonald and Mardoqueu (2019) used the regionalization of areas in the Amazon to more effectively identify the relationship between malaria cases and deforestation, making clear the importance that native areas have for local public health.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible to associate dengue incidence and Ae. aegypti density with areas of unconsolidated urban sprawl lacking urban infrastructure [39,51].…”
Section: Discussionmentioning
confidence: 99%